2021
DOI: 10.1007/s40123-021-00447-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Adverse Effects of Topical Glaucoma Medications on Trabeculectomy Outcomes Using the Glaucoma Medications Intensity Index

Abstract: Introduction:Trabeculectomy is commonly performed for glaucoma when medications are unable to control disease progression or have intolerable adverse effects. Previous studies have suggested that a higher number of and/or longer treatment duration with preoperative topical glaucoma medications are associated with a higher risk of trabeculectomy failure, but most of these studies lack quantification of exposure. The aim of this study was to investigate the relationship between preoperative exposure to topical g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 27 publications
2
2
0
1
Order By: Relevance
“…In order to demonstrate the impact of age, we therefore need more longitudinal observational studies on large populations. Previous studies have shown that a substantial risk factor for failure of the filtering operation is the cumulative number of topical antiglaucoma medication [36][37][38], and this is consistent with our results. Conjunctival goblet cells are reduced in eyes undergoing long-term topical glaucoma treatment, while fibroblasts, macrophages, and lymphocytes are increased [39,40].…”
Section: Discussionsupporting
confidence: 93%
“…In order to demonstrate the impact of age, we therefore need more longitudinal observational studies on large populations. Previous studies have shown that a substantial risk factor for failure of the filtering operation is the cumulative number of topical antiglaucoma medication [36][37][38], and this is consistent with our results. Conjunctival goblet cells are reduced in eyes undergoing long-term topical glaucoma treatment, while fibroblasts, macrophages, and lymphocytes are increased [39,40].…”
Section: Discussionsupporting
confidence: 93%
“…For that reason, the AGV showed more benefit than nonvalved GDD in terms of immediate lowering of IOP postoperatively, while in nonvalved GDD it needed 4–6 weeks of longer waiting time until the capsule fibrosis around the plate was formed to function. While protective factor was duration of antiglaucoma mediation shorter than 10 months prior to GDD implantation with unadjusted HR 0.45 (95%CI: 0.25, 0.82), p =0.009, which was implied that the longer duration of antiglaucoma treatment the more failure in GDD implantation similar to the report of associate factors for failure outcome in trabeculectomy by Wong et al 19 Corneal complications such as endothelial cell loss leading to corneal decompensation in our study were comparable with the results reported by Beatson et al by 5% (79 from 1610 eyes) and risk factors were as follows: older age, postoperative hypotony, tube-cornea touch, Fuchs' dystrophy, iridocorneal endothelial (ICE) syndrome, and higher number of previous glaucoma surgeries. 20 Because the anterior chamber location of the tube placement was one of the identifiable risks of corneal decompensation, the drawback of tube placement in the sulcus or in pars planar 21 when possible instead could lead to more incidents of tube occlusion or tube malposition, that occurred at a rate of 11.1% in this study.…”
Section: Discussionsupporting
confidence: 72%
“…Preservatives in topical glaucoma medications, such as polyquaternium-1 (PQ-1) and benzalkonium chloride (BAK), may disrupt the ocular surface, activate proinflammatory cytokines, cause squamous metaplasia of the conjunctival epithelium, fibrosis of Tenon’s capsule, and decrease the number of goblet cells [ 217 , 218 ]. The long-term use of topical medications may induce subclinical or clinical conjunctival inflammatory changes and reduce the success rate of GFS [ 219 ]. The cornea is a major part of the ocular surface and is a tissue that undergoes minute remodeling during homeostasis.…”
Section: Resultsmentioning
confidence: 99%